Difluoromethylation of N-arylsulfonyl hydrazones with difluorocarbene leading to difluoromethyl aryl sulfones. Issue 85 (30th August 2016) - Zheng, Qu-Tong; Wei, Yun; Zheng, Jian; Duan, Ya-ya; Zhao, Gang; Wang, Zong-Bao; Lin, Jin-Hong; Zheng, Xing; Xiao, Ji-Chang
Abstract : Difluoromethylation of N -arylsulfonyl hydrazones with difluorocarbene generated from difluoromethylene phosphobetaine (Ph3 P + CF2 CO2 − ) is described to give various difluoromethyl aryl sulfones. Abstract : The difluoromethylation of N -arylsulfonyl hydrazones with difluorocarbene generated from difluoromethylene phosphobetaine (Ph3 P + CF2 CO2 − ) to give various difluoromethyl aryl sulfones is described.